Transforming Islamic Pedagogy Through Digital Innovation and Ethical Frameworks in Post-Pandemic Higher Education Systems - Huzaiman Hushin (Al Husna: Jurnal Ilmiah Pendidikan Agama Islam, 2024)
The post-pandemic era has accelerated the digital transformation of higher education institutions worldwide, compelling Islamic higher education systems to reconsider their pedagogical approaches, technological infrastructures, and ethical foundations. This study aims to examine how Islamic pedagogy can be transformed through digital innovation while maintaining ethical principles rooted in Islamic educational philosophy. Employing a qualitative library research approach, the study analyzes recent scholarly literature, policy reports concerning digital learning, Islamic pedagogy, educational technology, and ethical frameworks in higher education. The findings indicate that digital innovation has significantly enhanced learning accessibility, pedagogical flexibility, collaborative engagement, and personalized learning experiences within Islamic higher education. However, challenges related to digital ethics, academic integrity, data privacy, technological inequality, and the preservation of Islamic values remain critical concerns. The study proposes an integrated framework that combines digital innovation with Islamic ethical principles, emphasizing responsible technology use, critical digital literacy, learner-centered pedagogy, and value-based educational practices. The novelty of this research lies in developing a conceptual model that systematically connects digital transformation, Islamic pedagogy, and ethical governance within post-pandemic higher education systems. The study concludes that sustainable educational transformation requires the integration of technological advancement with ethical and spiritual dimensions to ensure that digital innovation contributes meaningfully to holistic human development and educational excellence